Influence of Hydrology and Sanitation on Groundwater Coliform Contamination in Some Parts of Western Bengal Basin: Implication to Safe Drinking Water - Dey, Uttiya; Sarkar, Soumyajit; Duttagupta, Srimanti; Bhattacharya, Animesh; Das, Kousik; Saha, Sumedha; Mukherjee, Abhijit (Frontiers in Water, 2022)
Access to clean water has been identified as one of the primary Sustainable Development Goals. Rapid urbanization is going on in developing nations creating additional pressure on water resources in most of these places which in turn also affects individuals which is largely reliant on proper sanitation and drinking water quality. In addition, open sanitation practice is becoming major public health problem in rural as well as in some urban areas in India. Groundwater contamination by pathogenic bacteria sourced from both sanitation system and surface water is becoming one of the major concerns now-a-days. The residents of the Ganges river basin in India are already stressed with natural arsenic pollution as well as other various types of water pollution, microbial pollution from sanitation is a new addition to it. A field-based hydrogeological investigation with the identification of sanitation sites (surface and sub-surface) was conducted in some parts of the Ganges basin, in and around a lower order distributary river, River Churni in West Bengal state, to identify the natural and human influences on sanitation- drinking water pollution in a highly populated part of South Asia. Groundwater was found to be contaminated severely with total (TC) and fecal (FC) coliform bacteria. The abundance of TC was found to be the highest in monsoons season (78%) than in pre-monsoon (48%) and post-monsoon (29%) seasons. Results revealed that the groundwater samples from shallow depths and close to sanitation sites were highly contaminated with coliform bacteria than the deeper and higher distant (> 30 m distance) ones. Shallow groundwater samples near to surface water (River Churni) source, other than sanitation sites, showed elevated TC levels. The occurrence of coliform bacteria in studied groundwater samples was observed to be positively correlated with conductivity, TDS, TOC, chloride, and sulfate, while the abundance was restricted by pH and temperature of groundwater. Thus, improper sanitation systems and contaminated surface water were identified as one of the major sources of pathogenic contamination of groundwater-sourced drinking water in the studied area. Whereas improper human practices further complicate the scenario which needs to be managed properly.